Effects of Lysine–Lysine Dipeptide on Serum Amino Acid Profiles, Intestinal Morphology, and Microbiome in Suckling Piglets - Deng, Yuankun; Han, Hui; He, Liuqin; Deng, Dun; Wang, Jing; Yin, Yulong; Li, Tiejun (Frontiers in Nutrition, 2022)
Small peptides are more energy-saving and efficiently absorbed compared with amino acids. Our study amied to evaluate the effect of Lys-Lys dipeptide on the improvement of growth performance, amino acid metabolism, and gut development in sucking piglets. 28 newborn suckling piglets were orally administrated with 0.1%, 1%, and 5% Lys-Lys dipeptide for 21 days, respectively. Our results showed that Lys-Lys dipeptide has no significant effect on the growth performance and intestinal morphology compared with the control group. We also found that 1% Lys-Lys dipeptide significantly increased the concentrations of serum Lys, Thr, Phe, and Pro while decreasing Cys compared with the control group. Similarly, 5% Lys-Lys dipeptide markedly increased the concentrations of serum Lys, Iso, Thr, Asp, Glu, and Pro compared with the control group. Moreover, Lys-Lys dipeptide downregluated the expression of jejunal SLC7A1, SLC7A2, and SLC15A1 and ileal SLC7A2, respectively. Additionally, Lys-Lys dipeptide decreased the microbiota richness indices and the relative abundance of Bacteroidales. In conclusion, Lys-Lys dipeptide influenced serum amino acids and intestinal microbiota but failed to affect growth performance.